(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This interdisciplinary research study titled "Right to Adequate Food: Social Work Interventions for Building Indigenous Knowledge, Gender, and Resilience" investigates the multifaceted dimensions of the Right to Adequate Food. Drawing from diverse academic sources, the research explores social, economic, and legal aspects, emphasizing governance structures related to climate change in South Asia. It also delves into the sociological lens of caste dynamics, employing a case study on the appointment of bhojanmaata to analyze the intersectionality of caste and gender within educational settings. The study extends its focus to gender issues in food security, examining differential impacts on women and considering the nutritional needs of pregnant and nursing women. Furthermore, the research emphasizes the intersectionality of the right to food with indigenous knowledge and cultural narratives, drawing insights from various sources, including governmental reports and grassroots initiatives. Ultimately, the study seeks to contribute valuable insights for social work interventions that promote inclusivity, equality, and resilience in the context of food security.